PENGGUNAAN MEDIA ALAM TERHADAP KEMAMPUAN EKSPLORASI SENI ANAK USIA DINI DI PAUD AISYIYAH RANTING V MARTAPURA USIA 3-4 TAHUN - Murni, Farida; Nisa, Uswatun; Zulkarnaen, Muhammad; Baiti , Noor (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve the artistic exploration skills of children aged 3–4 years through the use of natural plant media at PAUD Aisyiyah Ranting V Martapura. The research employed a Classroom Action Research (CAR) design conducted in two cycles, consisting of the stages of planning, implementation, observation, and reflection. The findings indicated a significant improvement in children's artistic exploration skills in each cycle. In the pre-cycle stage, most children were categorized as Not Yet Developed (NYD), accounting for 71.43% (10 children). After the implementation of Cycle I, the children's abilities improved, with the majority reaching the Beginning to Develop (BD) category at 71.43% (10 children), while 28.57% (4 children) achieved the Developing as Expected (DE) category. By the end of Cycle II, children's development showed remarkable progress, with 78.57% (11 children) categorized as Developing as Expected (DE) and 21.43% (3 children) reaching the Very Well Developed (VWD) category. This improvement was supported by hands-on activities using natural plant media, such as leaf printing, leaf classification, watering plants, and painting with plant roots, which successfully enhanced children's participation, creativity, and confidence in expressing their imagination. The study concludes that the use of natural plant media is effective in improving the artistic exploration skills of children aged 3–4 years at PAUD Aisyiyah Ranting V Martapura.